Knowledge Management Values of Al-Ta’alum\In Ms 1900:2005 Quality Management System: A Case Study of Kolej of Islam Pahang Sultan Ahmad Shah (Kipsas) - Yaakub, M.H.; Ahmad Khan, A.F.; Ismail, I. (American Scientific Publishers, 2015)
This study aims to evaluate the willingness of knowledge sharing and acquisition behaviors among KIPSAS’s employees to comply with the values of Al-Ta’allum. These are aligned with the principles of knowledge management. The main objective is to identify the differences in knowledge sharing of the staff with their knowledge acquisition behavior. Thus, identifying the state of readiness among staff. This study utilizes an exploratory approach to examine these phenomena. Related documents were analyzed to get an overview of the factors and values of Al-Ta’allum that have been identified and examined within the study. Questionnaires were sent to 129 respondents from academic and non-academic staffs. But only 62 responses were gathered. There were also differences when the respondents were divided and analyzed according to responsibilities and gender. Within the context of this article, we found the overall relevance of values stipulated in Al-Ta’allum to staff of KIPSAS. This study is concerned with examining the knowledge sharing behavior of staff in a PHEI. It highlights the differences in their knowledge sharing and acquisition behavior. This allows management and planner of such institutions to plan the Knowledge Management (KM) initiatives and processes with these special value indicators such as Al-Ta’allum to be taken into consideration. Based on the result, KIPSAS is able to manage knowledge sharing activities in a more effective method.